Respostas

2013-08-29T18:45:52-03:00
Reta => função afim.  f(x) = ax + b

P(3,0)                                                             Q(2,-3)
 a(3) + b = 0                                                   a(2) + b = - 3
3a + b = 0                                                       2a + b = - 3

Sistema:

3a + b = 0
2a + b = - 3               Multiplicamos o de baixo por (-1) e somamos o resto.

3a + b = 0
-2a - b = 3

a = 3

Com o valor de "a" achamos o "b":

3a + b = 0
3.3 + b = 0
9 + b = 0
b = - 9

lei de formação => f(x) = 3x - 9           Item C